The theory of agency and breastfeeding. Issue 3 (4th March 2017) - Ryan, Kath; Team, Victoria; Alexander, Jo
Abstract : Objective : In this paper, we apply psychological agency theory to women's interviews of their breastfeeding experiences to understand the role of agency in relation to breastfeeding initiation, maintenance and duration. Design : Qualitative, video interviews were collected from 49 women in the UK from a wide range of ethnic, religious, educational and employment backgrounds about their breastfeeding experiences. We undertook secondary analysis of the data focusing on their accounts of vulnerability and agency. Findings : Women's agency was impacted by a variety of factors including their own vulnerability, knowledge, expectations and experience, the feeding environment and the support of health professionals in sharing decision-making and dealing with uncertainty. Conclusion : Health professionals as co-agents with women are well positioned to maintain, enhance or restore women's sense of agency. Breastfeeding goals should be included in women's birth plans. Training related to agency, continuity of care, and staffing and workload management supported by national breastfeeding policies could improve breastfeeding rates and experiences.